HUBUNGAN POWER OTOT TUNGKAI DENGAN KEMAMPUAN AKURASI SHOOTING PADA PERMAINAN SEPAK BOLA SISWA SMAN 1 LAWA - Ahmad Risal; Hasanuddin Jumareng; Badaruddin (Universitas Halu Oleo, 2022)
The purpose of this study was to determine the relationship between leg muscle power and shooting accuracy in the soccer game of SMAN 1 Lawa students. The population in this study was the total number of class XI students of SMAN 1 Lawa, amounting to 210 people using purposive random sampling technique. The data of this study were analyzed using the statistical technique of 0.05% product moment. In the study, it was concluded that there was a relationship between leg muscle power and shooting accuracy in the soccer game of SMAN 1 Lawa students, where Rxy = 0.48> r table 0.361. While the coefficient of determination (r^2) = 0.24 or 24%. This shows that the level of correlation between the variable leg muscle power (X) and shooting accuracy in the soccer game of SMAN 1 Lawa students (Y) is at a moderate correlation. Besides, 76% is influenced by elements of other physical conditions. The results of this study indicate that there is a significant relationship between leg muscle power and shooting accuracy in the soccer game of SMAN 1 Lawa students.